2012
DOI: 10.1063/1.4748297
|View full text |Cite
|
Sign up to set email alerts
|

Dust-acoustic waves and stability in the permeating dusty plasma. II. Power-law distributions

Abstract: The dust-acoustic waves and their stability driven by a flowing dusty plasma when it cross through a static (target) dusty plasma (the so-called permeating dusty plasma) are investigated when the components of the dusty plasma obey the power-law q-distributions in nonextensive statistics. The frequency, the growth rate and the stability condition of the dust-acoustic waves are derived under this physical situation, which express the effects of the nonextensivity as well as the flowing dusty plasma velocity on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Since nonextensive statistics was proposed in 1988 [1], the theoretical successes in both astronomy & astrophysics [2][3][4][5] and space plasmas [6][7][8][9][10][11] have shown that the new statistical method may be suitable for describing many astrophysical systems. In this work, we apply the methods of nonextensive statistics to study the nonequilibrium property of a pure self-gravitating system.…”
Section: Introductionmentioning
confidence: 99%
“…Since nonextensive statistics was proposed in 1988 [1], the theoretical successes in both astronomy & astrophysics [2][3][4][5] and space plasmas [6][7][8][9][10][11] have shown that the new statistical method may be suitable for describing many astrophysical systems. In this work, we apply the methods of nonextensive statistics to study the nonequilibrium property of a pure self-gravitating system.…”
Section: Introductionmentioning
confidence: 99%
“…Eq. (4) has also be applied to establish new characteristics in the nonequlibrium space plasmas with the power-law distributions [17,18,50,51]. In this work, on the basis of the q-kinetic theory in NSM we will study the q-parameter for the rotating astrophysical systems with the q-distribution, generally including the self-gravitating systems and the space plasmas.…”
Section: -----------------------------------------mentioning
confidence: 99%
“…For example, in self-gravitating systems, NSM has been applied to study the negative heat capacity [2,3], the equilibrium structure and stability [4][5][6], the dark matter distributions [7][8][9] and the rotations [10][11][12][13][14], etc. In the space plasmas, NSM has been applied to study various waves and instability [15][16][17][18] and solar wind [19][20][21], and properties of the plasmas with the κ-distributions [22][23][24][25][26][27][28][29][30][31]. In particular, we have recently seen detailed studies and deep understanding of the κ-distributions in the space plasmas and their statistical properties [27][28][29][30][31].…”
Section: -----------------------------------------mentioning
confidence: 99%
“…It is especially worth mentioning that for recent years nonextensive statistical mechanics (NSM) based on Tsallis entropy has received great attention and very wide applications to a variety of interesting problems in physics, chemistry, astronomy, biology, engineering and technology [19]. NSM has also been the statistical base of the kappa-distributions observed in space plasmas [20][21][22][23][24]. In NSM, the power-law distribution can be derived using the extremization of Tsallis entropy.…”
mentioning
confidence: 99%